Attitude of Adolescent Girls Towards Teaching about Body Image - Juodeikytė, Viktorija; Norkus, Andrius (Jaunųjų mokslininkų darbai, 2016)
Body image is a subjective perception of our body, in the broadest sense it is defined as “corporeality experience” exposed to biological and psychological components of human nature. Body image is an important precondition for self-esteem and mental health at all stages of our life. The aim of this research is to reveal adolescent girls’ attitude towards teaching about body image at school. According to the research findings, only a third of the surveyed adolescent girls are satisfied with their appearance. The respondents stated that school curriculum does not affect their body image perceptions, and the majority of the surveyed did not even know about the opportunity to choose a health module. Every second surveyed wanted additional lectures about positive body image.